The Individual Differences of Indonesian High School Students’ Academic Interest in English as a Foreign Language - Teresa Angelina Kaluge; Sisilia Setiawati Halimi (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This study aims to examine individual differences, using gender as the exploratory variable and age as the covariate on academic interest among Indonesian high school students learning English. The research used a quantitative method. Data were collected virtually using an online questionnaire from 324 learners in four private urban high schools. The instrument used was the Academic Interest Scale for Adolescents (AISA). The process of data analysis consisted of confirmatory factor analysis, calculating Cronbach’s alpha, descriptive statistics, MANOVA, and MANCOVA. Four constructs were found valid and reliable: emotion, value, knowledge, and engagement. After validating the interest scale, data analysis disclosed the following results. Firstly, among the four constructs of academic interest, the value dimension was the highest and the knowledge factor the lowest, whereas emotion and engagement were in the middle position. Secondly, student gender differentiated significantly only in engagement. Thirdly, only the correlation between age and engagement was significant and positive in academic interest and student age. Lastly, considering student age, all the constructs except knowledge were differentiated by gender, where girls outperformed boys. These findings are valuable inputs for teachers, policymakers, and educational researchers in dealing with student language learning in Indonesian high schools.